Discovery of the genus Maikona Matsumura, 1928 (Noctuidae: Agaristinae) from India with the description of a new species - Irungbam, Jatishwor Singh; Fric, Zdenek Flatynek (Zootaxa, 2024)
The genus Maikona Matsumura, 1928 is reported for the first time from India with the description of a new species, Maikona mayodiana n. sp., from the Mayodia pass, Arunachal Pradesh, India. The diagnoses of the new species with similar congeners along with illustrations of its habitus, and genitalia are provided. A distributional map of the members of the genus is also provided.